Framing Adult Learners: From Heroic Victim to Capable Comrade - Alisa Belzer; Amy Pickard (Adult Education Research Conference, 2014)
This qualitative research synthesis of portrayals of adult literacy learners identified five types of “characters” that can have a powerful impact on how the “action” of practice, policy, and research are shaped.